Interactions among Cupressaceae pollen, air pollutants and meteorology in the urban and suburban areas of Beijing, China - Qin, Xiaoxin; Li, Yiyin; Zhang, Hongxing; Liu, Wenjun; Zhao, Xinyi (Scientific reports, 2025)
Atmospheric pollutants alter the physicochemical properties of pollen allergens, and raise a high risk of co-exposure to more aeroallergens in the allergic population. It is necessary to reveal the relationships between them and the impacts of meteorology on them both. Herein, synchronous data of aerobiology, pollution and meteorology at the same location are used to investigate the correlation between Cupressaceae pollen (major allergen in Norther China) and atmospheric pollutants, and their association with meteorological factors at different timescales in the urban and suburban areas of Beijing, China. In this research, the correlation between allergenic pollen, air pollutants and meteorological factors may display distinct patterns at daily and hourly timescales. Daily concentration of Cupressaceae pollen was positively correlated with PM 2.5 and O 3 . Hourly pollen concentration exhibited positive correlation with NO x and PM 2.5 during high-pollen episodes. Increasing temperature and decreasing relative humidity after sunrise facilitate pollination, causing hourly pollen peak. Temperature exhibited a strong positive correlation with daily and hourly O 3 concentrations. Highly humid conditions largely decreased allergenic pollen and O 3 concentrations but increased NO x and PM 2.5 concentrations. In the urban area, local winds considerably impacting on hourly pollen peaks were associated with high levels of NO x and PM 2.5 . Concentration weighted trajectory (CWT) results indicated that allergenic pollen and O 3 may have some common potential source areas. This research will help us to get a better understanding of the linkage between allergenic pollen and air pollutants, and their dynamics under varying meteorological conditions, and provide effective support on addressing respiratory allergies on the risk of co-exposure for allergenic pollen and air pollutants in the urban and suburban areas of Beijing city.